EFEKTIFITAS PERNIKAHAN MUBARAKAH DI PESANTREN HIDAYATULLAH BALIKPAPAN DALAM TINJAUAN MAQASHID SYARIAH - Paryadi Paryadi; Zikri Darussamin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The family divorce rate in Indonesia is high and concerning because it is increasing every year. This is because of the variety of problems and challenges in each family member in Indonesia. Despite various government efforts to build family integrity. The Hidayatullah Islamic Boarding School in Balikpapan with its mubarakah marriage program since 1977 is trying to provide a solution. The results showed that the mubarakah marriage carried out by the Hidayatullah Islamic Boarding School Balikpapan from registration, debriefing, matchmaking, marriage contracts, walimah and dowry in accordance with maqashid shari'ah, namely the protection of ushul khamsah (religion, soul, mind, lineage and property). Mubarakah marriages are shari'a and official, meaning that they are in accordance with Islamic law and government regulations that are effective in time, place and cost.